1988
DOI: 10.1002/cne.902780207
|View full text |Cite
|
Sign up to set email alerts
|

Sequential development of connections between striate and extrastriate visual cortical areas in the rat

Abstract: In these experiments we have asked whether the projection from the rat's primary visual cortex, area 17, to the extrastriate visual cortical area 18a is formed in a sequence and whether that sequence resembles the pattern of inside-out cortical neurogenesis. For this purpose fluorescent retrograde tracers were injected into area 18a at different postnatal ages (P1, P5, adult). Animals survived until 3-4 weeks of age, after migration is complete and neurons have arrived at their final laminar location. In the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…However, labeling in sublayer VIb has been previously observed (see Divac et a]., 1987aDivac et a]., , 1987bFonseca et al, 1988;Reep and Goodwin, 1988). Moreover, injections of retrograde tracers into the lateral agranular fields of the motor cortex (Donoghue and Parham, 1983) and primary visual cortex (Miller and Vogt, 1984;Coogan and Burkhalter, 1988) also labeled cells in sublayer VIb. In a recent study using a combination of HRP, WGA:HRP, and fluorescent dyes, Koralek et al (1990) did not observe extensive labeling of sublayer VIb in the rat SI.…”
Section: Discussionmentioning
confidence: 78%
“…However, labeling in sublayer VIb has been previously observed (see Divac et a]., 1987aDivac et a]., , 1987bFonseca et al, 1988;Reep and Goodwin, 1988). Moreover, injections of retrograde tracers into the lateral agranular fields of the motor cortex (Donoghue and Parham, 1983) and primary visual cortex (Miller and Vogt, 1984;Coogan and Burkhalter, 1988) also labeled cells in sublayer VIb. In a recent study using a combination of HRP, WGA:HRP, and fluorescent dyes, Koralek et al (1990) did not observe extensive labeling of sublayer VIb in the rat SI.…”
Section: Discussionmentioning
confidence: 78%
“…Coogan and Burkhalter (1988) demonstrated that such corticocortical connections form in an inside-out pattern, with the infragranular layers of striate cortex reaching their extrastriate targets 4 FIG. 4.…”
Section: Timing Of Collateral Outgrowthmentioning
confidence: 99%
“…In fact, rodent feedforward connections resemble more closely the lateral connections in monkey (Felleman and Van Essen 1991). A likely reason for this difference is that feedforward connections in rodents originate from layers 2-6 (Coogan and Burkhalter 1988), whereas, in monkey, layers 2 and 3 are the main sources of these connections (Felleman and Van Essen 1991). From a developmental perspective, Dehay and Kennedy (2007) have argued that layers 2 and 3 in primates are different from layers 2 and 3 in mice, which lack the computational components of primate cortex.…”
Section: Cortical Hierarchymentioning
confidence: 99%